EFFICIENCY OF SERVICE ACTIVITIES FOR SERVICING PRODUCTS OF MACHINE-BUILDING ENTERPRISES - N. V. Arsenieva; L. M. Putyatina; N. V. Tarasova (Вестник университета, 2020)
The importance of improving the efficiency of the system of service activities for the maintenance of machine-building products has been outlined. Individual types of service and their features have been analysed. The indicators that determine the effectiveness of service activities by type, the criteria for their evaluation and the most favorable trends in the process of working out the production of certain types of goods have been considered. It has been noted that the service of machine-building products is quite an expensive item of the production activities of enterprises. To justify the costs of warranty service, it is necessary to have certain statistics of product failures and its individual elements for their additional production in order to ensure timely provision to the consumer. The analysis showed that the costs of all types of goods servicing are an important indicator of its organization by enterprises. Statistics for keeping records of all types of product maintenance allows you to improve its production, plan the production of spare parts and reduce the cost, which is an important element of competitiveness.